2013
DOI: 10.2298/psi130525001d
|View full text |Cite
|
Sign up to set email alerts
|

Mood congruence effect in autobiographical recall: Is mood a mediator?

Abstract: In the present study we test the hypothesis that the effect of mood congruence in autobiographical recall is underlain by mood. Thirty-eight female participants were subjected to positive, negative and neutral mood inductions, and then asked to recall three personal memories. Participants’ mood was assessed using self-report questionnaires and by electromyograph (EMG) measurements of corrugator supercilii and zygomaticus major muscle activity. We replicated the congruence effect between the mood inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Others observed increases in proportion rates for recalling positive/negative memories in a congruent versus incongruent mood in the range of .07–0.156 (e.g., Berntsen, 2002; Bullington, 1990; Ehrlichman & Halpern, 1988; Sakaki, 2007). Several studies have also indicated that mood shifts the valence of recalled memories in a mood-congruent direction (Drače, 2013; Drače & Desrichard, 2013; Drače et al, 2015), although such effects may not only influence memories for mood-congruent cues. Miranda and Kihlstrom (2005), for example, showed that memories recalled for positive, negative, or neutral cues were all rated as more or less pleasant depending on the induced mood state, indicating a generalized mood-congruent shift in the phenomenological experience of memory recall.…”
Section: Revisiting MCMmentioning
confidence: 99%
“…Others observed increases in proportion rates for recalling positive/negative memories in a congruent versus incongruent mood in the range of .07–0.156 (e.g., Berntsen, 2002; Bullington, 1990; Ehrlichman & Halpern, 1988; Sakaki, 2007). Several studies have also indicated that mood shifts the valence of recalled memories in a mood-congruent direction (Drače, 2013; Drače & Desrichard, 2013; Drače et al, 2015), although such effects may not only influence memories for mood-congruent cues. Miranda and Kihlstrom (2005), for example, showed that memories recalled for positive, negative, or neutral cues were all rated as more or less pleasant depending on the induced mood state, indicating a generalized mood-congruent shift in the phenomenological experience of memory recall.…”
Section: Revisiting MCMmentioning
confidence: 99%
“…Neuroimaging studies examining the influence of emotion in encoding and retrieval also provide evidence in support of this 75 , 76 . Further, recent empirical studies based on human participants also offer support to this theory 77 . However, there seem to be no computational models of this phenomenon.…”
Section: Introductionmentioning
confidence: 79%
“…If this was the case, it would mean that the BMIS was merely an indirect measure of the semantic aspects activated by the situation: a hypothesis that seems to be disproved by several factors. For example, Drace and Desrichard (2013) found that BMIS correlated with a non-verbal measure of affect (i.e., EMG activity of muscles corrugator supercilia and zygomaticus major) that should be less sensitive to semantic priming and that both measures mediated the relation between mood inductions and autobiographical recall. On the other side, the BMIS has been found to be sensitive to mood manipulation using a variety of induction procedures, even those with low semantic content (e.g., Niedenthal & Setterlund, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…When addressing this question, researchers have usually tried to isolate the influence of the affective state by selecting mood induction procedures that are not supposed to activate semantic concepts, congruent with the material to be recalled. However, as suggested by some authors (e.g., Drace & Desrichard, 2013) there are two problems with this approach. First, studies of this type often produce contradictory findings, with some concluding that the mood congruence effect is not caused by an individual's affective state (Mayer, Gayle, Meehan, & Haarman, 1990;Rholes et al, 1987;Riskind, 1983;Riskind, Rholes, & Eggers, 1982), and others suggesting the opposite (Ehrlichman & Halpren, 1988;Kumari, Hemsley, Cotter, Checkley, & Grey, 1998;Schnall & Laird, 2003).…”
mentioning
confidence: 99%